2016
DOI: 10.1111/jace.14439
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐Iron Oxide as Energy Storage Medium in Rechargeable Oxide Batteries

Abstract: Rechargeable oxide batteries (ROB) comprise a regenerative solid oxide cell (rSOC) and a storage medium for oxygen ions. A sealed ROB avoids pumping loss, heat loss, and gas purity expenses in comparison with conventional rSOC. However, the iron oxide base storage medium degrades during charging–discharging cycles. In comparison, CaFe3O5 has improved cyclability and a high reversible oxygen storage capacity of 22.3 mol%. In this study, we analyzed the redox mechanism of this compound. After a solid‐state synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…contains 4% substitution of excess Fe for Ca (making the overall composition from the refinements Ca 0.952(8) Fe 3.040(8) O 5 ), which they suggest may tip the balance between the energies of the CO and CA states, raising the possibility that the occurrence of the phase separation may be sample dependent, and may be sharply dependent on composition. A further recent study of CaFe 3 O 5 as a potential oxide-ion storage material in solid oxide fuel cells also used Mössbauer spectroscopy and was largely consistent with the work of Gerardin et al 12 , detecting only one phase at low temperature 14 . However, it also noted that the room temperature Mössbauer spectrum deviated from the usual 3:2:1 ratio for magnetic features, and concluded that an incommensurate antiferromagnetic hyperfine field distribution was the simplest model to account for the spectrum.…”
Section: Introductionsupporting
confidence: 67%
“…contains 4% substitution of excess Fe for Ca (making the overall composition from the refinements Ca 0.952(8) Fe 3.040(8) O 5 ), which they suggest may tip the balance between the energies of the CO and CA states, raising the possibility that the occurrence of the phase separation may be sample dependent, and may be sharply dependent on composition. A further recent study of CaFe 3 O 5 as a potential oxide-ion storage material in solid oxide fuel cells also used Mössbauer spectroscopy and was largely consistent with the work of Gerardin et al 12 , detecting only one phase at low temperature 14 . However, it also noted that the room temperature Mössbauer spectrum deviated from the usual 3:2:1 ratio for magnetic features, and concluded that an incommensurate antiferromagnetic hyperfine field distribution was the simplest model to account for the spectrum.…”
Section: Introductionsupporting
confidence: 67%
“…After examining a series of metal oxide combinations, the authors concluded that the only oxide that can be easily oxidized and reduced within the envisaged operational window with the desired stability was the combination of iron oxide and calcium oxide. [ 9,18 ] The study suggests that CaFe 3 O 5 is a promising ESU material owing to its good storage capacity and resistance against degradation. [ 18 ] Figure 11 shows a schematic of the sintering mitigation mechanism.…”
Section: Improving Intermediate Temperature Performance Of Somarbsmentioning
confidence: 99%
“…[ 9,18 ] The study suggests that CaFe 3 O 5 is a promising ESU material owing to its good storage capacity and resistance against degradation. [ 18 ] Figure 11 shows a schematic of the sintering mitigation mechanism. Upon reduction, it transforms to Fe and CaO via Ca 2 Fe 2 O 5 which prevents metallic iron from forming large agglomerates.…”
Section: Improving Intermediate Temperature Performance Of Somarbsmentioning
confidence: 99%
“…A promising approach for hydrogen storage is the thermochemical reduction and oxidation of metals (M)/metal oxides (M n O m ) [11,15,30], which can be generally described by:…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 8YSZ is extremely expensive, so that the authors, themselves, recommended not to apply it in future work [16]. In further publications, they focused on the application of clearly less expensive additives like CaCO 3 [30].…”
Section: Introductionmentioning
confidence: 99%